Research Progress on Laser-Assisted Precision Machining Technology - Qimeng Liu; Jie Liu; Zhe Ming; Bo Cui; Jian Wang (Micromachines)
As a revolutionary advanced manufacturing technology, the core of laser-assisted machining technology lies in the innovation of traditional machining technology. It uses a laser to precisely modify the surface of the workpiece material through clever integration. This process can lead to significant changes in the microstructure, thermodynamic properties, and physical properties of the workpiece’s cutting layer, greatly facilitating the removal of material by the cutting tool. Especially for difficult-to-process materials, this technology can effectively solve the processing problems they face. This not only improves the processing accuracy, but also ensures the processing quality, making it possible to process difficult-to-process materials with high precision and high quality. This article comprehensively summarizes the latest research progress in laser-assisted precision machining technology and deeply summarizes the specific mechanism of laser-assisted machining technology on the surface of workpiece materials. The influence of laser-assisted machining technology on the cutting characteristics of machining materials is elaborated in detail, providing a theoretical basis for the application of this technology. Finally, the future development direction of laser-assisted machining technology is prospected.